IMPLEMENTASI PERDA KOTA BANDUNG NOMOR 09 TAHUN 2018 TENTANG PENGELOLAAN SAMPAH SEBAGAI UPAYA TERWUJUDNYA CIVIC PARTICIPATION MASYARAKAT KOTA BANDUNG (Studi Deskriptif Masyarakat di Kelurahan Cipedes, Kecamatan Sukajadi Kota Bandung) - Nisa Nur Aifah, - (2020)
NISA NUR AIFAH (1601609). "IMPLEMENTATION OF BANDUNG CITY REGULATION NUMBER 09 YEAR 2018 REGARDING WASTE MANAGEMENT AS AN EFFORT TO REALIZE CIVIC PARTICIPATION IN BANDUNG COMMUNITY" (Descriptive Study Of The Community In The Cipedes Village, Sukajadi District, Bandung City) Citizenship education as a forum for accommodating forms of community participation so that they become productive citizens and can contribute to the activities of the surrounding community. Evidence of the implementation of the Bandung City Regulation No. 09/2018 concerning waste management as an effort to realize civic participation, the purpose of this research is to carry out a form of community participation following policies in waste management in the Cipedes Exit, Sukajadi sub-district, Bandung city in a qualitative approach with descriptive research methods of collecting data through documentation study, observation and interviews with the aim of knowing the activities of the community in Cipedes Village on waste management. Through the triangulation technique, data analysis techniques will be obtained. So that through data reduction, data presentation and data conclusions can be analyzed thoroughly. The results of the study indicate that (1) the form of community participation in Cipedes Village is seen from the start of knowing the origin of waste, sorting waste and how to dispose of waste. (2) there are obstacles in the low awareness of the community in themselves towards waste management so that there are still people who litter (3) There are various efforts made by the local government of the city of Bandung in overcoming obstacles to implementing waste programs by improving and improving services and facilitating facilities infrastructure to realize civic participation. Keywords: Citizenship Education, Bandung City Regulation Number.09 of 2018, Waste Management, Civic Participation.